Antibacterial Activity in Extract of Bauhinia. Vahlii (BioMedical Research in Microbiology (BMR Microbiology) (ISSN: 2349-4603), 2024)
Bauhinia species have a long history of traditional medicinal applications. The aim of the present study was to evaluate the antibacterial potential of the ethanol extracts of B. vahlii roots, barks, and seeds was tested for antimicrobial activity against bacterial water borne pathogens using agar well diffusion assay the antibacterial activities were found to be species independent. Effectiveness of the extracts against different bacterial strains was measured in terms of zone of inhibition in millimeters. The values determined were compared with the positive control (Ampicilin) with highest antimicrobial activity against all tested microorganisms.